The important roles of ERAP1, ERAP2 genes polymorphisms and their DNA methylation levels in pulmonary tuberculosis - Shi-Hong Su; Xue-Qian Cai; Yong-Huai Li; Ai-Hui Xu; Qian Huang; Hua Niu; Qing-Hai You; Geng-Yun Sun (BMC Infectious Diseases)
Abstract Background Genetic variations in endoplasmic reticulum aminopeptidase (ERAP1, ERAP2) genes are associated with the pathogenesis of multiple diseases, including infectious diseases. The objective of our study was to assess whether ERAP1, ERAP2 genes polymorphisms and methylation levels affect the risk of pulmonary tuberculosis (PTB). Methods We genotyped ten single nucleotide polymorphisms (SNPs) in ERAP1, ERAP2 genes among 497 PTB patients and 502 controls by SNPscan technique. Additionally, we detected the ERAP1, ERAP2 genes methylation levels in 98 PTB patients and 97 controls through Illumina Hiseq platform. Results Our results showed that the GG genotype, G allele frequencies of ERAP2 gene rs2549782 were significantly increased in PTB patients compared to controls, and rs2549782 polymorphism was related to the increased risk of PTB under recessive model. In addition, no significant relationship was found between ERAP1 gene rs13167972, rs17086651, rs469783, rs26618, rs3734016, ERAP2 gene rs17524572, rs1230358, rs2549794, rs117041256 and PTB susceptibility. Among PTB patients, the frequencies of rs17524572 TT genotype, T allele were significantly associated with drug-induced liver injury, and rs1230358, rs2549782, rs2549794 polymorphisms were linked to the occurrence of fever. Haplotype analysis of ERAP2 gene suggested that the frequency of CTGGT haplotype was higher, while the frequency of CTGTT haplotype was lower in PTB patients. When compared with controls, the ERAP1 methylation level was lower in PTB patients, while the ERAP2 methylation level was significantly increased. Moreover, rs1230358 polymorphism was found to affect the ERAP2 methylation level. Conclusion The ERAP2 rs2549782 variant and altered methylation levels of ERAP1, ERAP2 genes were related to susceptibility to PTB.